1991
DOI: 10.1128/mcb.11.10.5005
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA binding by monomeric, homodimeric, and potentially heteromeric forms of the thyroid hormone receptor.

Abstract: Binding of the thyroid hormone receptor (TR) to thyroid hormone-responsive elements (TREs) is crucial for regulation of gene expression by thyroid hormone. The TR binds to each half-site of a palindromic TRE separately, as a monomer, or simultaneously, as a homodimer. In addition, the TR monomer interacts with a 42-kDa protein that may be responsible for an increase in the apparent size and stability of the TR-TRE complex after incubation with liver nuclear extract. The multiple DNA-binding forms of the TR con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
90
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(96 citation statements)
references
References 57 publications
(73 reference statements)
6
90
0
Order By: Relevance
“…While retinoid-dependent transactivation by RXR is mediated in part by RXR homodimers (66), RXR is also able to form heterodimers with TR and VDR (7,18,36,37,46,48,64,65). In each case, target gene binding by the nuclear hormone receptor is greatly enhanced by its partnership with RXR.…”
mentioning
confidence: 98%
“…While retinoid-dependent transactivation by RXR is mediated in part by RXR homodimers (66), RXR is also able to form heterodimers with TR and VDR (7,18,36,37,46,48,64,65). In each case, target gene binding by the nuclear hormone receptor is greatly enhanced by its partnership with RXR.…”
mentioning
confidence: 98%
“…The thyroid hormone receptor is also capable of binding to thyroid hormone response elements (TREs) as a monomer or homodimer, but the latter complex is known to dissociate in the presence of thyroid hormone (T 3 ) (8 -11). More recently, it has been shown that TR as well as receptors for vitamin D 3 , retinoic acid (RAR), and eicosanoids form heterodimeric complexes with an auxiliary factor, the retinoid X receptor (RXR) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The TR⅐RXR heterodimer binds TREs with higher affinity than TR alone and remains stable in the presence of T 3 (8 -11), suggesting that this complex mediates ligand-dependent transcriptional activation.…”
mentioning
confidence: 99%
“…The v-Erb A I-box sequence also contributes to stabilizing receptor homodimer complexes against disruption by T3 Although c-Erb A homodimers assemble with high affinity on many DNA elements in the absence of hormone, these c-Erb A homodimers typically dissociate in the presence of T3, whereas RXR/c-Erb A heterodimers are stable to T3 (Lazar et al, 1991;Forman et al, 1992;Ribeiro et al, 1992;Yen et al, 1992Yen et al, , 1994Miyamoto et al, 1993;Piedrafita et al, 1995;Yoh and Privalsky, 2001). This T3-driven dissociation of homodimers may, in fact, function to drive an exchange of the c-Erb A/c-Erb A homodimers implicated in transcriptional repression for the RXR/c-Erb A heterodimers involved in transcriptional activation.…”
Section: Substitutions In the V-erb A I-box Enhance Homodimerization mentioning
confidence: 99%
“…A third mode of DNA recognition by c-Erb A is the ability to bind to suitable response elements as a protein monomer (Lazar et al, 1991;Forman et al, 1992;Darling et al, 1993;Glass, 1994;Katz and Koenig, 1994;Koenig, 1995, 1998;Wahlstrom et al, 1996;Subauste, 2002, 2003). These c-Erb A monomers can be observed on DNA elements containing a single half-site, or as part of a mixed population of monomers, homodimers, and heterodimers on response elements containing two or more halfsites.…”
Section: Substitutions In the V-erb A I-box Enhance Homodimerization mentioning
confidence: 99%
See 1 more Smart Citation